# Let f(x) = x + 8 and g(x) = x^{2} - 6x - 7. Find f(g(2)).

**Solution:**

Given, f(x) = x + 8

g(x) = x^{2} - 6x - 7

We have to find f(g(2)).

f(g(x)) = f(x^{2} - 6x - 7)

= (x^{2} - 6x - 7) + 8

= x^{2} - 6x - 7 + 8

f(g(x)) = x^{2} - 6x + 1.

Put x = 2 in the above expression,

f(g(2)) = (2)^{2} - 6(2) + 1

= 4 - 12 + 1

= 5 - 12

f(g(2)) = -7

Therefore, the value of f(g(2)) is -7.

## Let f(x) = x + 8 and g(x) = x^{2} - 6x - 7. Find f(g(2)).

**Summary:**

Let f(x) = x + 8 and g(x) = x^{2} - 6x - 7. The value of f(g(2)) is -7.

Math worksheets and

visual curriculum

visual curriculum